Investigation of low-temperature thermochemical energy storage for water heating in residential application - Zhang, Yong (2025)
This study aims to develop a low-temperature thermochemical energy storage (TCES) water heating system for domestic use, designed to integrate with low-temperature sustainable energy sources like solar energy. The goal is to improve the utilization of renewable energy in residential applications, reduce reliance on fossil fuels, and lower greenhouse gas emissions.